PEGEMI (Peran Generasi Milenial) Dalam Mewujudkan Kesetaraan Gender Melalui Pendekatan Media Sosial - Larasati, Monica; Rozan, Hafiz; Saputra, Iqbal Dwi; H, Ali Fikri Bustanul; Munir, Achmad; Radianto, Denny Oktavina (VISA: Journal of Vision and Ideas, 2023)
Gender equality is a global goal that has become the concern of the world community. One important factor in achieving gender equality is the role of the millennial generation or what is often referred to as generation Y. The millennial generation has a very important role in fighting for gender equality. Through this research, the authors discuss the role of the millennial generation in realizing gender equality. The author uses a qualitative descriptive method by conducting interviews with five millennials who are active in the gender equality movement. The findings from this study indicate that the millennial generation has a good understanding of gender equality and they also actively participate in the gender equality movement. The millennial generation has also taken the initiative to bring gender equality issues into the public sphere through social media and social activities. However, there are still many challenges faced by the millennial generation in fighting for gender equality, such as gender stereotypes and discrimination that still exist in society. Therefore, the millennial generation needs to continue to struggle and work together with related parties to achieve gender equality. Keywords: millennial generation, gender equality